El departamento de documentación del congreso de los diputados y la documentación parlamentaria - García Sánchez, M.ª Isabel (Revista General de Información y Documentación, 2002)
The role played in parliamentary life by the information sector is of undeniable importance. The Information Unit in the Congreso de los Diputados (founded in 1984) is organized in three areas which concentrate on the treatment and control of more than 2000 periodical publications, the management of publications received on special support, Web page administration, and the dissemination of information produced both by itself and by other bodies, which is asked for by Deputies or offered through selective dissemination of information.